Harmonic Analysis of a Single Phase Modulated Inverter - Md. Imran Azim; S. M. Mohiuddin (Institute of Advanced Engineering and Science, 2016)
This paper portrays an approach of an analysis that provides information regarding the presence of harmonics at the inverter output terminal. It is certainly true that harmonics cause unbalance and excessive neutral currents, interference in nearby communication networks and disturbance to other consumers. More importantly, torque pulsations in electric motor drives are caused by them. Thus, the minimization of the harmonics contained in the output of a single phase current controlled inverter undergoing hysteresis modulation technique is important so as to get rid of these detrimental effects. A model of an LC low pass filter has been provided in this paper for harmonics reduction purpose, as it blocks the harmonics and passes approximately a sinusoidal output. Moreover, the paper contains the method of Fast Fourier Transform (FFT) for fulfilling the desire of understanding not only the fundamental component but also the harmonics component flawlessly. It has been found from the simulation that the Total Harmonic Distortion (THD) in ideal case is 0%. On the other contrary, during the presence of harmonics, it steeps to 41.415% that can be mitigated to 0.0092% by implementing an LC low pass filter in a precise manner.